The Use of MQ 3 Sensor in Measuring Benzo[a]Pyrene Compound From Wood Husk Combustion Process with Robotdyn Uno R3 WiFi - Putra, Alga Pradipta Ananda; Wardoyo, Arinto Yudi Ponco; Anggraeni, Dewi; A, Renetha Salma Myesha (Master Program in Mechanical Engineering, Gunadarma University, 2024)
BaP (Benzo[a]pyrene) is one of the Polycyclic Aromatic Hydrocarbon (PAH) compounds produced from the combustion process of organic materials such as wood husks. This study aims to utilize the MQ 3 sensor integrated with RobotDyn Uno R3 WiFi microcontroller to measure BaP concentration in gas emissions from wood husk combustion. The MQ 3 sensor was chosen for its sensitivity to BaP compounds. In this experiment, the MQ-3 sensor achieved an accuracy of 85% with a BaP measurement range from 0 to 26 ppm. Measurements were conducted on wood husks with BaP concentrations varying from 0 to 4 ppm. The results indicate that this method is effective for real-time monitoring of BaP levels in wood husk combustion processes, with potential applications in controlling toxic gas emissions from such processes